1989
DOI: 10.1038/340307a0
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin inhibits the terminal differentiation of human keratinocytes

Abstract: In the epidermis proliferation of keratinocytes is restricted to the basal layer, which is in contact with the basement membrane, and cells undergo terminal differentiation as they move upwards through the suprabasal layers. In stratified cultures of human keratinocytes, upward migration is a consequence, not a cause, of terminal differentiation and occurs because keratinocytes become less adhesive to their substratum and to one another. Most keratinocytes can be induced to differentiate to completion by placi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
250
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(258 citation statements)
references
References 25 publications
7
250
1
Order By: Relevance
“…Since the average transit time from the basal to the cornified layers is about 1 month in normal human epidermis we are reasonably confident that the stem cells were targeted in the original infection. Although the YPRF mutant used in the grafts did not affect keratinocyte proliferation in culture or mediate ECM adhesion 18 (data not shown) we have evidence that it can suppress suspension-induced terminal differentiation 15,16 (data not shown) and thus we cannot rule out the possibility that expression of the YPRF mutant confers a selective advantage on the transduced cells. It will now be interesting to test other transduced genes in the experimental model.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since the average transit time from the basal to the cornified layers is about 1 month in normal human epidermis we are reasonably confident that the stem cells were targeted in the original infection. Although the YPRF mutant used in the grafts did not affect keratinocyte proliferation in culture or mediate ECM adhesion 18 (data not shown) we have evidence that it can suppress suspension-induced terminal differentiation 15,16 (data not shown) and thus we cannot rule out the possibility that expression of the YPRF mutant confers a selective advantage on the transduced cells. It will now be interesting to test other transduced genes in the experimental model.…”
Section: Discussionmentioning
confidence: 86%
“…For the experiments to be reported the chick ␤ 1 integrin subunit was chosen as the transduced gene because expression and function could be monitored on a cell-bycell basis and because of the role of ␤ 1 integrins in regulating keratinocyte terminal differentiation. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…24 In the skin, however, the loss of contact is a stimulus for differentiation for the keratinocytes. 25 The hepatocytes have no contact with laminin containing structured basement membrane. Yin et al 26 reported that isolated hepatic stem cells expressed biliary or hepatocytic phenotypes in culture, depending on the presence or absence of basement membrane matrix (Matrigel).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin-mediated adhesion also primes monocytes for inflammatory responses [51]. Finally, the expression of involucrin, which is associated with terminal differentiation of cultured keratinocytes under semisolid conditions, is inhibited by the integrin-ligand fibronectin [52].…”
Section: Regulation Of Proliferation Survival and Differentiation Bmentioning
confidence: 99%